Treatment for a rare case of phenazopyridine-induced methemoglobinemia: a case report and mini-review - Coyne, Brendan M.; Ishaq, Syed M.; Thota, Anjani; Thakkar, Badal (Frontiers in Medicine, 2025)
Methemoglobinemia is a condition caused by elevated levels of methemoglobin (MetHb) in the blood, a reduced form of hemoglobin that cannot properly bind to oxygen, interfering with delivery to tissues. If left untreated, this condition can be fatal. Phenazopyridine, an over-the-counter urinary tract analgesic, has been reported to cause methemoglobinemia in rare instances. In the present case, a 67-year-old patient demonstrated hypoxia and oral cyanosis in the setting of chronic phenazopyridine use and chronic obstructive pulmonary disease (COPD). A “chocolate-brown” coloration of his blood and an elevated MetHb level of 14.5% confirmed the diagnosis of methemoglobinemia. He was treated with methylene blue, ascorbic acid, bronchodilators, steroids, and supportive oxygen. This regimen led to a gradual improvement in the patient’s clinical condition, including his hypoxia, cyanosis, and MetHb levels. This report illustrates a rare, unique case of phenazopyridine-induced methemoglobinemia and acute hypoxic respiratory failure in a patient with pre-existing COPD. In such patients, effective management requires a careful treatment approach directed at both methemoglobinemia and COPD.